Antioxidant capacity of seminal plasma measured by TAS Randox(R) - Fingerova, Helena; Novotny, Jiri; Barborik, Jiri; Brezinova, Jana; Svobodova, Magda; Krskova, Milena; Oborna, Ivana (Biomedical papers, 2007)
Background: An imbalance between reactive oxygen species (ROS) generation in sperm and antioxidant capacity of seminal plasma has been linked to male infertility. The antioxidant power of biological fl uids can be evaluated either by measurement of individual antioxidants or total antioxidant capacity (TAC). The aim of this study was to assess whether TAS Randox(R) can also be used for seminal plasma antioxidant capacity estimation..Material and Methods: Freshly thawed aliquots of seminal plasma and blood serum of 38 males from infertile couples and 24 healthy normospermic controls were simultaneously assayed using TAS Randox(R) reagents on the Hitachi Modular P800 Analyzer. Semen analysis was performed according to WHO guidelines. ROS in fresh sperm suspension in phosphate buffered saline was measured by chemiluminescence immediately after separation of seminal plasma.Results: Semen analysis showed that in our study group only 14 males were normospermic and 24 males had mostly combined pathologies. The medians for ROS production were similar in both the study and the control groups (4850 and 5450 RLU/min, resp). Seminal plasma TAS levels were significantly lower (p < 0.02) in the study group while blood serum TAS levels were similar in both groups. A significant positive correlation (p < 0.05) between TAS in seminal plasma and serum was found, seminal plasma levels being on average 1.4 times higher.Conclusions: The TAS Randox(R) kit may be used for clinical studies intended to identify decreased antioxidant power in the seminal fl uid of infertile men.
Keywords: Oxidative stress/Antioxidant capacity/TAS Randox(R)/Seminal plasma/Blood serum/Male infertility